Catalytic aerobic phenolhomo- and cross-coupling reactions with copper complexes bearing redox-active guanidine ligands - Schön, Florian; Kaifer, Elisabeth; Himmel, Hans-Jörg (Chemistry - a European journal, 2019)
Due to their large importance in synthetic chemistry, catalytic C−C coupling reactions of phenols are currently intensively studied. Herein, new copper catalysts for the C−C coupling reaction of phenols using dioxygen as a green oxidizing reagent are reported. By using redox-active guanidine ligands, the activity as well as chemoselectivity in the cross-coupling reaction of non-complementary phenols (between an electron-rich phenol and a less nucleophilic second phenol) is significantly improved. Based on the collected data for several test reactions, a reaction mechanism is proposed.